Polydeoxyribonucleotide: A Promising Biological Platform to Accelerate Impaired Skin Wound Healing - Mariarosaria Galeano; Giovanni Pallio; Natasha Irrera; Federica Mannino; Alessandra Bitto; Domenica Altavilla; Mario Vaccaro; Giovanni Squadrito; Vincenzo Arcoraci; Michele Rosario Colonna; Rita Lauro; Francesco Squadrito (Pharmaceuticals, 2021)
The normal wound healing process is characterized by a complex, highly integrated cascade of events, requiring the interactions of many cell types, including inflammatory cells, fibroblasts, keratinocytes and endothelial cells, as well as the involvement of growth factors and enzymes. However, several diseases such as diabetes, thermal injury and ischemia could lead to an impaired wound healing process characterized by wound hypoxia, high levels of oxygen radicals, reduced angiogenesis, decreased collagen synthesis and organization. Polydeoxyribonucleotide (PDRN) has been used to improve wound healing through local and systemic administration thanks to its ability to promote cell migration and growth, angiogenesis, and to reduce inflammation on impaired wound healing models in vitro, in vivo and clinical studies. In light of all these observations, the aim of this review is to provide a full overview of PDRN applications on skin regeneration. We reviewed papers published in the last 25 years on PubMed, inserting “polydeoxyribonucleotide and wound healing” as the main search term. All data obtained proved the ability of PDRN in promoting physiological tissue repair through adenosine A2A receptor activation and salvage pathway suggesting that PDRN has proven encouraging results in terms of healing time, wound regeneration and absence of side effects.